Effects of Sarcolemmal Background Ca2+ Entry and Sarcoplasmic Ca2+ Leak Currents on Electrophysiology and Ca2+ Transients in Human Ventricular Cardiomyocytes: A Computational Comparison - Streiff, Molly E.; Sachse, Frank B. (Frontiers in Physiology, 2022)
The intricate regulation of the compartmental Ca2+ concentrations in cardiomyocytes is critical for electrophysiology, excitation-contraction coupling, and other signaling pathways. Research into the complex signaling pathways is motivated by cardiac pathologies including arrhythmia and maladaptive myocyte remodeling, which result from Ca2+ dysregulation. Of interest to this investigation are two types of Ca2+ currents in cardiomyocytes: (1) background Ca2+ entry, i.e. Ca2+ transport across the sarcolemma from the extracellular space into the cytosol, and (2) Ca2+ leak from the sarcoplasmic reticulum (SR) across the SR membrane into the cytosol. Candidates for the ion channels underlying background Ca2+ entry and SR Ca2+ leak channels include members of the mechano-modulated transient receptor potential (TRP) family. We used a mathematical model of a human ventricular myocyte to analyze the individual contributions of background Ca2+ entry and SR Ca2+ leak to the modulation of Ca2+ transients and SR Ca2+ load at rest and during action potentials. Background Ca2+ entry exhibited a positive relationship with both [Ca2+]i and [Ca2+]SR. Modulating SR Ca2+ leak had opposite effects of background Ca2+ entry. Effects of SR Ca2+ leak on Ca2+ were particularly pronounced at lower pacing frequency. In contrast to the pronounced effects of background and leak Ca2+ currents on Ca2+ concentrations, the effects on cellular electrophysiology were marginal. Our studies provide quantitative insights into the differential modulation of compartmental Ca2+ concentrations by the background and leak Ca2+ currents. Furthermore, our studies support the hypothesis that TRP channels play a role in strain-modulation of cardiac contractility. In summary, our investigations shed light on the physiological effects of the background and leak Ca2+ currents and their contribution to the development of disease caused by Ca2+ dysregulation.